Advances in 2D materials based mixed-dimensional heterostructures photodetectors: Present status and challenges - Somvanshi D.; Jit S. (My University, 2025)
The unique and exceptional properties of two-dimensional (2D) materials have opened unprecedented opportunities for exploring novel 2D phenomena for optoelectronic applications. The dangling bond-free interface of 2D materials enables them to be combined with any other dimensional (i. e. 0D, 1D, and 3D) materials without requiring any direct chemical bond formation and lattice matching. The resultant materials obtained by combing the 2D materials with 0D, 1D, or 3D materials form a broad class of materials commonly known as mixed-dimensional (MD) heterostructures. These new emerging materials have continuously been explored for photodetection applications due to their tunability of operating wavelengths. This article presents a brief critical review of some state-of-the-art works of the emerging MD heterostructures-based photodetectors from the last decade. A review of various types of MD heterostructures such as 0D/2D, 1D/2D, and 2D/3D, and their fundamental issue related to band alignment type, interlayer coupling, and charge & energy transfer for photodetection applications have been discussed in the detail. The relevant challenges for developing MD heterostructures-based high-performance broadband photodetectors are also discussed with an outlook for future developments. © 2023 Elsevier Ltd